Comparison of clinical signs and bacterial isolates of postpartum endometritis in holstein dairy cows in Iran (Veterinary Science Development, 2017)
The aim of this study was to determine the uterine bacteria in cows with endometritis and to compare other characteristics in cases of endometritis without bacterial growth, with Trueperella pyogenes (Arcanobacterium pyogenes) or other bacteria. In total, 86 Holstein cows with postpartum endometritis from 13 commercial dairy herds were sampled once between 21-35 days postpartum. We used several diagnostic techniques for endometritis such as external observation, vaginal exam, rectal palpation, ultrasonography, and cervical and uterine cytological examination. Clear mucus with flakes of pus (E1), mucopurulent discharge (E2), and purulent discharge (E3) are three groups of endometritis. A transcervical double-guarded swab was used for bacterial sampling. The samples were cultured aerobic and anaerobically and biochemical tests were used for differentiation. Measurements were compared between groups: A, no growth (n=47); B, positive bacterial growth without T. pyogenes (n=21); and C, positive bacterial growth with T. pyogenes (n=18). There were no differences (P>0.05) in uterine wall thickness, body condition score (BCS) and milk yield between the groups. The uterine horn diameter was largest in groups A (4.30±0.88) in comparison with groups B (4.81±1.17) and C (5.53±2.17) (P